De la genealogía del arte - Pérez Rincón, Germán Alfonso (CALLE14: revista de investigación en el campo del arte, 2011)
This article reflects on the conference The Dionysian Vision of the World and the book The Birth of Tragedy, and tries to interpret Nietzsche's point of view about the hidden and meaningful connections that appeared during the birth of the Greek tragedy from the encounter of two principles: The Apollonian and the Dionysian.